The effect of mutations in the lid region of Thermomyces lanuginosus lipase on interactions with triglyceride surfaces: a multi-scale simulation study - Willems, N; Lelimousin, M; Skjold-Jorgensen, J; Svendsen, A; Sansom, M (Elsevier, 2017)
Lipases naturally function at the interface formed between amphiphilic molecules and the aqueous environment. Thermomyces lanuginosus lipase (TLL) is a well-characterised lipase, known to exhibit interfacial activation during which a lid region covering the active site becomes displaced upon interaction with an interface. In this study, we investigate the effect the amino acid sequence of the lid region on interfacial binding and lid dynamics of TLL. Three TLL variants were investigated, a wild-type variant, a variant containing an esterase lid region (Esterase), and a Hybrid variant, containing both wild-type lid residues and esterase lid residues. Multiple coarse-grained molecular dynamics simulations revealed that the interfacial binding orientation of TLL was significantly affected by the nature of amino acids in the lid region, and atomistic simulations indicated effects on the structural dynamics of the lid itself. The atomistic simulations, as well as steered molecular dynamics simulations, also indicated that the Esterase lid region was less flexible than the wild-type lid region, whereas the Hybrid variant displayed superior lid flexibility and stability in the open conformation both at the interface, and in aqueous solution. Additional experiments performed to investigate the activity and binding behaviour of the lipase variants indicated a slightly higher specific activity for the Hybrid variant compared to the wild-type variant, correlating the observations of increased lid flexibility. Together, these results are in line with previous experimental studies, highlighting the importance of the nature of the amino acid residues within the functional lid region of lipases, particularly regarding interfacial binding orientation, activation, and structural stability.